A Multicenter, Randomized, Double-Blind, Placebo-Controlled Study of Compound Glycyrrhizin Capsules Combined with a Topical Corticosteroid in Adults with Chronic Eczema. (30th March 2020) - Xu, Wei; Li, Yan; Ju, Mei; Lai, Wei; Lu, Xueyan; Shi, Huijuan; Shi, Weimin; Gu, Heng; Li, Linfeng
Abstract : Background . Glycyrrhizin is widely used in skin disorders, such as psoriasis, alopecia areata, and allergic diseases, but has not been extensively studied in patients with chronic eczema. Objective . To evaluate the efficacy and safety of oral compound glycyrrhizin (OCG) plus topical corticosteroid (TCS) in adults with chronic eczema. Methods . This was a multicenter, randomized, double-blind, placebo-controlled study in patients with chronic eczema ( n  = 199). Randomized participants from 6 centers in China received either 75 mg OCG capsules or placebo capsules three times a day and TCS (i.e., 0.1% mometasone furoate ointment) once a day for 28 days. Efficacy was determined by analyzing the mean change from the baseline using standardized measures including the Investigator's Global Assessment (IGA) score, Eczema Area and Severity Index (EASI), and the visual analogue scale score (VAS) of itching. Results . Decreases in absolute EASI were significantly greater in the OCG-treated group versus placebo on day 14 (−3.41 ± 1.41 vs. −2.71 ± 1.25, P < 0.001 ) and day 28 (−7.39 ± 1.71 vs. −6.64 ± 1.75, P = 0.003 ). OCG-treated patients also saw greater benefit in other EASI metrics including EASI-50 (96.8% vs. 87.9%, P = 0.021 ) and EASI-75 (47.9% vs. 21.2%, P < 0.001 ) on day 28 compared with placebo. The absolute IGA score reductions were also significantly greater in the OCG group than the placebo (all P < 0.05 ). In addition, proportions of patients who achieve clear (0) IGA scores or almost clear (1) IGA scores were significantly higher in the treated group than placebo on day 14 (22.8% vs. 6.2%, P = 0.001 ) and day 28 (93.5% vs. 79.4%, P = 0.005 ). Moreover, the proportions of patients with reduced pruritus were significantly greater in the treated group than placebo on day 28 (94.7% vs. 83.8%, P = 0.016 ) and eczema recurrence was notably less in the OCG group versus placebo (3.19% vs. 12.12%, P = 0.021 ). Eleven patients experienced adverse events, but there was no significant difference in the proportion of patients affected (3.0% vs. 8.5%, P > 0.05 ). The most common adverse events were edema of both lower limbs. Conclusion . For adults with chronic eczema, OCG capsules combined with TCS is an effective and well-tolerated treatment, suggesting that OCG may be a useful nonsteroidal agent with an additional effect for the treatment of chronic eczema by TCS.